Understanding depression and thoughts of self-harm in autism: A potential mechanism involving loneliness - Hedley, Darren; Uljarević, Mirko; Wilmot, Mathilda; Richdale, Amanda; Dissanayake, Cheryl (Research in autism spectrum disorders, 2018)
•This study examined mechanisms underpinning depression and thoughts of self-harm in Autism.•26% of participants met cut-off for depression, 21% reported thoughts of self-harm.•Loneliness acted on thoughts of self-harm indirectly through depression.•Highlights potential contribution of loneliness to depression and thoughts of self-harm in Autism. Individuals with Autism Spectrum Disorder (ASD) are at increased risk of suicidal ideation and behavior. This study characterized the inter-relationships between loneliness, depression and thoughts of self-harm in adults with ASD. Participants were 71 adults with ASD who completed questionnaires that provided information on loneliness, depression and thoughts of self-harm. Relationships between study variables were examined with correlations and a regression analysis. Two exploratory mediation models were then explored. Model 1 tested whether the relationship between depression and thoughts of self-harm was mediated through loneliness. Model 2 tested whether loneliness acted on thoughts of self-harm through depression. Twenty-six percent of participants met the clinical cut-off for depression and 21% reported thoughts of self-harm. Depressive symptoms, loneliness, and thoughts of self-harm were significantly correlated. Only Model 2, that identified an indirect pathway from loneliness, through depression to thoughts of self-harm, was supported. The mediator for this model accounted for 56.7% of the total effect. This study examined potential mechanisms underlying depression and thoughts of self-harm in ASD. These results highlight a possible contribution of loneliness to depression and thoughts of self-harm, suggesting treatment options that target loneliness may prove beneficial in improving mental health outcomes in ASD.